INDUSTRI JENANG MUBAROKFOOD CIPTA DELICIA DAN PENGARUHNYA TERHADAP SOSIAL EKONOMI MASYARAKAT GLANTENGAN TAHUN 1975-1998 (Jurusan Sejarah Fakultas Ilmu Sosial Universitas Negeri Semarang, 2012)
The research aims to analyze the history of the Industrial Jenang Mubarokfood Copyright Delicia, Industrial development Jenang Mubarokfood Copyright Delicia years 1975-1998 and the influence of the presence of Industry Jenang Mubarokfood Copyright Delicia against socioeconomic Glantengan. This study uses historical research, which includes four stages: heuristic, source criticism, interpretation, and historiography. Data collection techniques using interview techniques, study documents, and literature. Copyright Delicia Mubarokfood Jenang industry pioneered by married couples H. Mabruri and Hj. User Opinions in 1910 in the village of Glantengan Holy City District district. Copyright Delicia Mubarokfood Jenang industry launched three new brands, namely Mubarok, Mabrur, and Viva. Copyright Delicia Mubarokfood Jenang industry in the village Glantengan has brought many changes to people's lives. Any industry that directly reduce unemployment that the economy is getting better Glantengan. While not directly influence the Industry Jenang Mubarokfood Copyright Delicia is the emergence of new jobs outside the industry Jenang Mubarokfood Copyright Delicia, such as food stalls, grocery shop, and workshop .Keywords : Industry , Jenang Mubarokfood Copyright Delicia , Socio-Economic Penelitian bertujuan untuk menganalisis sejarah berdirinya Industri Jenang Mubarokfood Cipta Delicia, perkembangan Industri Jenang Mubarokfood Cipta Delicia tahun 1975-1998 dan pengaruh keberadaan Industri Jenang Mubarokfood Cipta Delicia terhadap sosial ekonomi masyarakat Glantengan. Penelitian ini menggunakan metode penelitian sejarah, yang meliputi empat tahap yaitu: heuristik, kritik sumber, interpretasi, dan historiogafi. Teknik pengumpulan data menggunakan teknik wawancara, studi dokumen, dan studi pustaka. Industri Jenang Mubarokfood Cipta Delicia dirintis oleh pasangan suami-istri H. Mabruri dan Hj. Alawiyah pada tahun 1910 di Desa Glantengan Kecamatan Kota Kabupaten Kudus. Industri Jenang Mubarokfood Cipta Delicia meluncurkan tiga merk baru, yaitu Mubarok, Mabrur, dan Viva. Industri Jenang Mubarokfood Cipta Delicia di Desa Glantengan telah banyak membawa perubahan bagi kehidupan masyarakat. Adanya industri itu secara langsung mengurangi pengangguran sehingga perekonomian masyarakat Glantengan semakin membaik. Sedangkan pengaruh tidak langsung adanya Industri Jenang Mubarokfood Cipta Delicia adalah munculnya lapangan pekerjaan baru di luar Industri Jenang Mubarokfood Cipta Delicia, seperti: warung makan, warung sembako, dan bengkel. Kata Kunci : Industri, Jenang Mubarokfood Cipta Delicia, Sosial Ekonomi